The effect of cell dose on the early magnetic resonance morphological outcomes of autologous cell implantation for articular cartilage defects in the knee: a randomized clinical trial - Niemeyer, Philipp; Laute, Volker; John, Thilo; Becher, Christoph; Diehl, Peter; Kolombe, Thomas; Fay, Jakob; Siebold, Rainer; Niks, Milan; Fickert, Stefan; Zinser, Wolfgang (The American journal of sports medicine, 2016)
Background: Although autologous chondrocyte implantation (ACI) has been established as a standard treatment for large full-thickness cartilage defects, the effe...
Gesehen am 03.11.2020